The Chestnut King / 3. - Wilson, Nathan D. (Wilson, Nathan D. 100 cupboards, 2010)
Twelve-year-old Henry York, finally reunited with his family, works with them and the Chestnut King, the long-deposed and mythic leader of the faeren people, to destroy Nimiane and her forces of evil.